Response of Different Levels of Nitrogen and Phosphorus on the Growth and Yield of French Bean (Bangladesh Journal of Scientific and Industrial Research, 2010)
Afield experiment on French bean was conducted in Old Brahmaputra Floodplain Soil of Jamalpur and Grey Terrace Soil of Joydebpur during 2005-2006 to find out the optimum rates of N and P for yield maximization. Four levels of nitrogen (0, 100, 150 and 200 kg ha-1) and 3 levels of phosphorus (0, 40 and 60 kg ha-1) were used in the experiment. Potassium (K) 80 kg, sulphur (S) 10 kg and 5 t cowdung ha-1 were applied as a basal dose. The experiment was laid out in a randomized complete block design with 12 treatments replicated 4 times. Nitrogen and phosphorus alone significantly influenced the pod yield of French bean. Among the N levels, the highest pod yield (13.33 t ha-1 at Jamalpur and 14.68 t ha-1 at Joydebpur) were obtained with 150 kg N ha-1. Among the P levels, the highest pod yield (12.35 t ha-1 at Jamalpur and 13.69 t ha-1 at Joydebpur) were obtained with 60 kg P ha-1. Interaction effect was not significant. However, highest pod yield (13.60 t ha-1 at Jamalpur and 15.05 t h-1 at Joydebpur) was obtained from 150 kg N plus 60 kg P ha-1. Economic analysis showed that 150 kg N plus 40 kg P ha-1 gave the highest gross margin of Tk. 1,66,684/ha. Key words: French bean; Nitrogen and phosphorus fertilization; Pod yield DOI: 10.3329/bjsir.v45i2.5716Bangladesh J. Sci. Ind. Res. 45(2), 169-172, 2010